Temporary Space: A Reflection upon ‘Good City Form’ - Rahma Hamidah; Evawani Ellisa (Journal of Architectural Design and Urbanism, 2023)
Temporary space is part of public space, which could be powerful enough to give the city its character and uniqueness. This study aims to investigate how “sense” and activities of temporary space created at Jalan Menpor Palsigunung, Depok, potent to distinguish the street's character. Analyses were done based on Kevin Lynch's theory in his book the Good City Form (1981). This qualitative study was conducted using empirical data through observation of the physical form and activities along both sidewalks of the street. This study's findings conclude that semi-permanent retailing features can create opportunities for placemaking. It is derived from how these features give meaning to places through repetitive and colourful physical forms and face-to-face trading activities that attract many people to participate.